#TITLE_ALTERNATIVE# - AZHARI YULIAN (NIM 15104001), EDWARD
The storing process of three dimensional (3D) spatial data from CAD (Computer Aided Design) system into GIS (Geographic Information System) database structure can't be done straightly because 3D geometric data in CAD is still arranged in a sphagetti format. To build a connection between CAD and GIS in the storing process of 3D spatial data, a certain program must be created in order to extract and convert geometric data of 3D object in CAD into topologic data in GIS. Boundary Representation (B-Rep) is a basic approach of 3D modeling that can be used to reconstruct the object by its surface. This approach can conduct the arrangement of 3D object topology which is ready to be inserted into a GIS database. Furthermore, the internal topology from each object will be correlated with its attributes and inserted together into a single database system. In this research, the structuring ability is still limited in a group of polyhedral objects. The object classes that will be reconstructed are Polyhedron, TriangleMesh, Surface, and Face. The object primitives that will be used in the topology arrangement for those four classes are node and face. Accessing process from and to the database system is using clientserver concept in a computer network. Based on the result of its testing, this program has a good capability in data structuring through a spatial database generation, that rounds up geometric and attribute entity of 3D object, and data presentation through a graphic visualisation and display of attribute data. Those abilities lead an important step for 3D GIS development in web environment.